PERANCANGAN ENTERPRISE ARCHITECTURE PADA YAYASAN SEKOLAH XYZ DENGAN MENGGUNAKAN TOGAF FRAMEWORK - Azhar, Nur Chalik; Imanda, Rahmi; Somoal, Muhammad Gabriel (ISTEK WIDURI, 2024)
In the world of education, enterprise architecture can be used to help the governance of an educational institution, one of which is a school. The XYZ Foundation has an organizational structure starting from the lowest level to the top to be able to carry out its business processes as an educational institution. By implementing enterprise architecture, it is hoped that operational processes will be in accordance with their respective functions and fields, have a collaborating IS and IT ecosystem so that they have the right output for data that is processed automatically. Students can get all the information they need, just by accessing the Student Portal. So that the XYZ Foundation can achieve the desired organizational vision to provide good services for its students so that they can be ready to compete with other competitors. The aim of this research is to propose an enterprise architecture design to the XYX Foundation, so that the use of technology within the school can be managed well and in accordance with school operations. The research method uses a qualitative approach, which consists of the stages of identifying problems and needs, collecting data, and adopting the TOGAF Framework. The result of this research is to produce an enterprise architecture design using the TOGAF Framework method which has been adapted to the problem conditions and needs of the XYX School Foundation. The conclusion of this research is that by implementing the enterprise architecture design that has been proposed, there are several benefits for the XYX School Foundation, such as as a guide for implementing IT governance, and helping to align IT governance with organizational goals. ABSTRAKDi dalam dunia pendidikan enterprise architecture dapat dimanfaatkan untuk membantu tata kelola sebuah institusi pendidikan yakni salah satunya adalah sekolah. Yayasan sekolah XYZ mempunyai struktur organisasi mulai dari tingkat paling bawah hingga paling atas untuk dapat menjalankan proses bisnisnya sebagai institusi pendidikan. Dengan menerapkan enterprise architecture diharapkan proses-proses operasional sudah sesuai dengan fungsi dan bidang masing-masing, Memiliki ekosistem sistem informasi (SI) dan teknik informasi (TI) yang berkolaborasi sehingga memiliki luaran yang tepat atas data yang diolah secara otomatis. Siswa dapat mendapatkan semua informasi yang dibutuhkan, dengan hanya mengakses portal siswa. Sehingga Yayasan sekolah XYZ dapat mencapai visi organisasi yang diinginkan untuk memberikan pelayanan yang baik bagi siswa-siswanya sehingga dapat siap bersaing dengan kompetitor lainnya. Tujuan pada penelitian ini adalah untuk mengusulkan sebuah rancangan enterprise architecture kepada Yayasan sekolah XYX, agar dalam pemanfaatan teknologi dilingkup sekolah dapat dikelola dengan baik dan sesuai dengan operasional sekolah. Metode dalam penelitian dengan menggunakan pendekatan kualitatif, dimana terdiri dari tahapan identifikasi masalah dan kebutuhan, pengumpulan data, dan adopsi TOGAF Framework. Hasil dari penelitian ini adalah menghasilkan rancangan enterprise architecture dengan menggunakan metode TOGAF Framework yang sudah disesuaikan dengan kondisi permasalahan dan kebutuhan Yayasan sekolah XYX. Kesimpulan dari penelitian ini adalah dengan menerapkan rancangan enterprise architecture yang telah diusulkan, bahwa terdapat beberapa manfaat untuk Yayasan sekolah XYX, seperti sebagai panduan untuk menerapkan tata kelola TI, dan membantu menyelaraskan antara tata kelola TI dan tujuan organisasi.